2014
DOI: 10.1158/1940-6207.capr-13-0259
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin: A Double Hit on Malignant Mesothelioma

Abstract: Inflammation is a key mediator in the development of malignant mesothelioma (MM) which has a dismal prognosis and poor therapeutic strategies. Curcumin, a naturally occurring polyphenol in turmeric, has been shown to possess anti-carcinogenic properties through its anti-inflammatory effects. Inflammasomes, a component of inflammation, control the activation of caspase-1 leading to pyroptosis and processing of pro-inflammatory cytokines, interleukin (IL)-1β and IL-18. In the present study, we investigate the ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 48 publications
0
43
0
Order By: Relevance
“…Inflammasomes have recently been shown to play an important role in mediating HMGB1 release from activated immune cells (Barlan et al, 2011; Craven et al, 2009; Lamkanfi et al, 2010; Lippai et al, 2013; Willingham et al, 2009; Willingham et al, 2007) or cancer cells (Miller et al, 2014). Thus, inflammasome-deficient mice or inflammasome inhibitor can inhibit HMGB1 release and protects mice against sepsis or I/R injury (Kamo et al, 2013; Xiang et al, 2011; Zhu et al, 2011b).…”
Section: Hmgb1 Releasementioning
confidence: 99%
“…Inflammasomes have recently been shown to play an important role in mediating HMGB1 release from activated immune cells (Barlan et al, 2011; Craven et al, 2009; Lamkanfi et al, 2010; Lippai et al, 2013; Willingham et al, 2009; Willingham et al, 2007) or cancer cells (Miller et al, 2014). Thus, inflammasome-deficient mice or inflammasome inhibitor can inhibit HMGB1 release and protects mice against sepsis or I/R injury (Kamo et al, 2013; Xiang et al, 2011; Zhu et al, 2011b).…”
Section: Hmgb1 Releasementioning
confidence: 99%
“…They showed that knockdown of TXNIP reduced inflammasome activation following asbestos treatment, indicating the important role of TXNIP in mediating inflammasome activation [111]. A recent study shows that curcumin, a polyphenol derived from turmeric was able to induce pyroptosis of mouse MM cells through activation of caspase-1 in the NALP3 inflammasome and the effect was ROS dependent [112].…”
Section: Asbestos-induced Cellular Signaling Pathwaysmentioning
confidence: 99%
“…After ensuring the integrity of the RNA samples, 500 ng of RNA was used for cDNA synthesis to be used in the Human EMT pathway RT 2 Profiler PCR Array as described previously. 13 Data obtained were then analyzed using the online SA Biosciences data analysis template.…”
Section: Pcr Arraymentioning
confidence: 99%
“…Ninety percent confluent LP9 cells were transiently transfected with On-Target Smart Pool siNLRP3 [ThermoScientific (Life Technologies), Grand Island, NY] or nontargeted control (siControl) constructs 32 hours before asbestos exposure to study the effects of reduced NLRP3 protein levels on MFT as previously described. 13 Additional experiments were performed with 4 single small interfering NLRP3 (siNLRP3) and nontarget controls [ThermoScientific (Life Technologies), Grand Island, NY] as described above. …”
Section: Transfection Experimentsmentioning
confidence: 99%